Aspergillus-Pseudomonas interaction, relevant to competition in airways. (28th February 2019) - Sass, Gabriele; Nazik, Hasan; Penner, John; Shah, Hemi; Ansari, Shajia R; Clemons, Karl V; Groleau, Marie-Christine; Dietl, Anna-Maria; Visca, Paolo; Haas, Hubertus; Déziel, Eric; Stevens, David A
Abstract: In airways of immunocompromised patients and individuals with cystic fibrosis, Pseudomonas aeruginosa and Aspergillus fumigatus are the most common opportunistic bacterial and fungal pathogens. Both pathogens form biofilms and cause acute and chronic illnesses. Previous studies revealed that P. aeruginosa is able to inhibit A. fumigatus biofilms in vitro . While numerous P. aeruginosa molecules have been shown to affect A. fumigatus, there never has been a systematic approach to define the principal causative agent. We studied 24 P. aeruginosa mutants, with deletions in genes important for virulence, iron acquisition, or quorum sensing, for their ability to interfere with A. fumigatus biofilms. Cells, planktonic or biofilm culture filtrates of four P. aeruginosa mutants, pvdD-pchE-, pvdD-, lasR-rhlR-, and lasR-, inhibited A. fumigatus biofilm metabolism or planktonic A. fumigatus growth significantly less than P. aeruginosa wild type. The common defect of these four mutants was a lack in the production of the P. aeruginosa siderophore pyoverdine. Pure pyoverdine affected A. fumigatus biofilm metabolism, and restored inhibition by the above mutants. In lungs from cystic fibrosis patients, pyoverdine production and antifungal activity correlated. The key inhibitory mechanism for pyoverdine was iron-chelation and denial of iron to A. fumigatus . Further experiments revealed a counteracting, self-protective mechanism by A. fumigatus, based on A. fumigatus siderophore production.